Using computer modeling during the design and reconstruction of hydropower facilities - Halych, Oksana; Nowak, Petr; Bílková, Eva (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The role of computer modeling during the design or reconstruction of the hydroelectric complexes is shown. The results of using the software HEC-RAS for the reconstruction of the Krimov Dam are given.